Effects of SA13353, a Transient Receptor Potential Vanilloid 1 Agonist, on Leukocyte Infiltration in Lipopolysaccharide-Induced Acute Lung Injury and Ovalbumin-Induced Allergic Airway Inflammation - Fumio Tsuji; Masaaki Murai; Kenji Oki; Hiroyuki Inoue; Minoru Sasano; Hiroyuki Tanaka; Naoki Inagaki; Hiroyuki Aono (Elsevier, 2010)
We recently demonstrated that SA13353, a transient receptor potential vanilloid 1 (TRPV1) agonist, reduced the severity of the symptoms of kidney injury, arthritis, and encephalomyelitis in disease models. Here, we investigated the effects of orally administered SA13353 on leukocyte infiltration in lipopolysaccharide (LPS)-induced acute lung injury and ovalbumin-induced allergic airway inflammation. In LPS-induced lung injury, SA13353 attenuated neutrophil infiltration and the increase of TNF-α and CINC-1 levels. In allergic airway inflammation, SA13353 tended to inhibit leukocyte infiltration and attenuated the increase of IL-4 and IL-12p40. These results suggest that somatosensory TRPV1 may play an anti-inflammatory role in lung inflammation. Keywords:: SA13353, transient receptor potential vanilloid 1, lung inflammation